Mixed problem with nonlocal boundary conditions for a third-order partial differential equation of mixed type - M. Denche; A. L. Marhoune (International Journal of Mathematics and Mathematical Sciences)
We study a mixed problem with integral boundary conditions for a third-order partial differential equation of mixed type. We prove the existence and uniqueness of the solution. The proof is based on two-sided a priori estimates and on the density of the range of the operator generated by the considered problem.